Myrcia machinazana (Myrtaceae), a new Amazonian species from southern Ecuador. Issue 1 (1st January 2021) - Pérez, Álvaro J.; Cevallos, Daniela; Zapata, Nicolás; Rea, Edison; Navarrete, Hugo; Kawasaki, Maria Lúcia
ABSTRACT: Myrcia machinazana, a new species from southern Amazonia in Ecuador is described and illustrated; additionally a distribution map is presented and its conservation status and relationships with other species are discussed. This new species is similar to Myrcia gigantifolia, but differs by its reddish to dark-brown indumentum on new growth (vs. new growth glabrous in M. gigantifolia ) and dense panicles with compactly arranged flowers and fruits (vs. panicles lax, flowers and fruits loosely arranged in M. gigantifolia ). A key to the Ecuadorian species of Myrcia is provided.